Estudo sobre a variável voseo da língua espanhola no cenario escolar - Carmona, Andréia Cristina Roder (2006)
Pupils are normally used to the traditional way of learning, few of them are aware of the fact that as they learn a foreign language they also learn about its culture and sociohistorical aspects. Reflections made on a multicultural scenario, in a schooling context, are extremely important in the development of Spanish Language teaching and learning, including the historical and sociocultural factors. Based on the theoretical concept of language which states that a language is a constituent of an individual, it is defended that the meaning of words derive from the context in which they are realized since they bring along ideological meanings marked historically and culturally. The teaching of a foreign language is the adequate space for this opening of a sociocultural and historical contact from the teacher’s part with other forms of knowing and interpreting reality and this teaching is efficient at the time it enables the teacher to see in the Other cultural and linguistic aspects which are different from his own. Therefore, the language teacher is of a crucial importance when he is teaching his student because teaching and learning a language is like teaching the teacher to perceive and understand perceptions which are different from the ones he presents. In order to reach this teaching and learning aim the historical and cultural studies of the Spanish language were focused which took into consideration the cultural plurality of the language so that it could be observed and written about the voseo variety more widely used in Latin America. In this dissertation, through an ethnographic work, it was aimed to research an analyze how a group of Spanish language teachers worked in their lessons linguistic diversity and, consequently, culture derived from the Spanish teaching as the identity of a person is always produced in relation to the Other, through interactions with the Other, which is constituted in and through the language. More objectively, it was investigated how and if a group of teachers worked on the voseo linguistic variety in their lessons. The same was done concerning the textbooks used by the teachers so as to check if there was any pedagogical practice to do with the teaching of the variant pronoun vos. The present study was ended with a suggestion on how help teachers in the teaching and learning process on the variant voseo in class. Teachers should be made aware that their work in class should also contemplate the linguistic varieties along with the institutionalized variety. It is believed that the results of this study can offer important contributions to teachers and, consequently, students will be benefited because they will learn more about the Spanish language through a work of awareness and tolerance when facing possible different points of view in different cultures.